ANSWER
• Distance:, 7.81
,
• Midpoint: ,(-4.5, -6)
Step-by-step explanation
The distance between two points (x₁, y₁) and (x₂, y₂) is given by the Pythagorean Theorem,
![d=\sqrt[]{(x_1-x_2)^2+(y_1-y_2)^2_{}}](https://img.qammunity.org/2023/formulas/mathematics/college/45856wqkd7p0q5e9z533lj5djbmuqd7gt9.png)
In this problem, the points are (-7, -9) and (-2, -3),
![\begin{gathered} d=\sqrt[]{(-7-(-2))^2+(-9-(-3))^2} \\ d=\sqrt[]{(-7+2)^2+(-9+3)^2}\text{ } \\ d=\sqrt[]{(-5)^2+(-6)^2}=\sqrt[]{25+36} \\ d=\sqrt[]{61}\approx7.81 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1nojjoismyy1r6w3y8lf35qd54s38v1onp.png)
Hence, the distance between P1 and P2 is 7.81 units.
To find the midpoint, we have to find the average between the coordinates of the points,
![(x_m,y_m)=\mleft((x_1+x_2)/(2),(y_1+y_2)/(2)\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/f5qp29qgza20dicv5mt8tnl5ltz9mwxe0n.png)
The midpoint in this problem is,
![(x,y)=\mleft((-7-2)/(2),(-9-3)/(2)\mright)=\mleft((-9)/(2),(-12)/(2)\mright)=(-4.5,-6)](https://img.qammunity.org/2023/formulas/mathematics/college/f0oqs6vv77ovn39dxjl3yv9jo4trc1z50z.png)
Hence, the midpoint between P1 and P2 is (-4.5, -6).